A escola enquanto espaço de formação para a democracia: percepções sobre o conteúdo da BNCC do ensino fundamental - SAMPAIO, Luane Tomé do Nascimento (2020)
This article has as main objective to understand how the democratizing function of the school is demonstrated in the Base Nacional Comum Curricular (BNCC) of elementary school. Having the document as the main source, as well as authors such as Guareschi, Touraine, Cury and Freire as theoretical support for the understanding of the functions that can be assigned to the school, with the intention of comparing the social function of the school as a space democratizing and the function of the State's ideological apparatus. In addition, the following normative references of the Brazilian educational politic, after Constitution of 88, will be analyzed: Lei nº 9.394 - Lei de Diretrizes e Bases da Educação Nacional e o Plano Nacional de Educação (PNE), characterizing the research as documentary and in bibliographic to investigate the possible functions performed by the school, how democracy appears in the National Basic Curricular Base of elementary education and if the BNCC establishes as a function of the school the promotion of a democratizing space.